PENINGKATAN PEMAHAMAN SISWA PADA MATERI TRANSFORMASI DENGAN MENGGUNAKAN DISCOVERY LEARNING (STUDI KASUS: SMPN 2 BANDA ACEH) - Haris Hidayat Ismail; R. Salasi; Bainuddin Yani; Ismail Ismail (Majelis Pendidikan Aceh, 2020)
The objective of this research is to figure out whether discovery learning can improve student's understanding of transformation concepts in mathematic. This study used a one-shot case study design. The research sample was twenty-six students from first-grade in class VII-3 of SMP Negeri 2 Banda Aceh, Indonesia. The concept of transformation was taught using the discovery learning model to the students. Our post-test result showed that the average score was 81.19 from a maximum score of 100. Eighty-eight percent of students passed the requirement of a passing grade. Meanwhile, the average score of the pre-test was 50 out of 100, and only fifty percent of students passed the passing grade. From the comparison of pre-test and post-test, we concluded that the discovery learning model can improve the student's ability in understanding the concept of transformation.